The Effect of Storage Time for Pooled Sera on Freezers on the Quality of Clinical Chemical Examination: Pengaruh Lama Penyimpanan Pooled Sera pada Freezer Terhadap Mutu Pemeriksaan Kimia Klinik - Maulidiyanti, Ellies Tunjung Sari; Purwaningsih, Nur Vita; Widiyastuti, Rahma; Samsudin, Rinza Rahmawati; Arimurti, Anindita Riesti Retno (Universitas Muhammadiyah Sidoarjo, 2021)
A common problem in clinical laboratories is maintaining the stability of serum analytes during sample storage. Samples are usually stored in the door (4–8°C) of the refrigerator for a short period of time or in the freezer (-20°C) for a longer period of time (pre-analytical stage) and subsequently, during post-analysis sample handling (storage time and temperature). This study aims to analyze the stability in this case is the storage time of pooled sera in the freezer at temperatures up to -18º C and in the refrigerator at temperatures up to 4°C for 3 months with the inspection parameters, namely cholesterol and triglycerides. This type of research is experimental, with a research design that is time series control group design. The sample in this study was a control serum in the form of pooled sera stored in the freezer and refrigerator which was checked for cholesterol and triglyceride levels every 2 weeks for 3 months or for 12 weeks. The results showed that the average calculation of cholesterol levels in pooled sera stored in the freezer was 142.07 mg/dL and the average cholesterol level examination stored in the refrigerator was 161.89 mg/dL then the average the examination of triglyceride levels in pooled sera stored in the freezer is 112.89 mg/dL and the average examination of triglyceride levels stored in the refrigerator is 140.46 mg/dL. Based on the analysis of the research results, it can be concluded that, there is an effect of storage time in the freezer on the stability of cholesterol levels and triglyceride levels.